KEBIJAKAN, KESENJANGAN DAN TANTANGAN TERHADAP TRANSFORMASI DIGITAL DALAM PENGEMBANGAN PENDIDIK DI SULAWESI SELATAN - Yasysyar Hidayat; Ansar Ansar (Jurnal Manajemen Pendidikan, 2026)
This literature review on digital transformation policies, gaps, and challenges in educator development in South Sulawesi aims to analyze policies, gaps, and challenges related to digital transformation. This study uses a systematic literature review approach by examining various sources published between 2021 and 2026. The analysis was conducted thematically, covering four main dimensions policy gaps, infrastructure and competency, organizational culture challenges, and the implications of digital transformation for educator professional development. The study results show that South Sulawesi has launched several innovative programs such as Smart Schools, Collaborative Digital Classes, digitalization of governance through Electronic Signatures, and Smart School Learning Communities. However, the implementation of these programs still faces significant infrastructure gaps, particularly in remote, island, and mountainous areas, where internet penetration in Sulawesi has only reached 68.35% the lowest in Indonesia. Cultural challenges such as resistance to change, low teacher digital literacy, and an organizational culture that does not support innovation also slow down the implementation of digital transformation.